Strategy Research on Accelerating Green and Low-Carbon Development under the Guidance of Carbon Peak and Carbon Neutral Targets. Issue 1 (June 2021) - Li, Yinan; Chen, Keren; Zheng, Nan; Cai, Qiyuan; Li, Yuanfei; Lin, Changyong
Abstract: Since September 2020, General Secretary Xi Jinping has made seven solemn promises to the world that China will achieve "carbon peak" by 2030 and "carbon neutral" by 2060. Under the guidance of carbon peak and carbon neutral targets, it has become an inevitable choice for China to accelerate green and low-carbon development. Developed countries started earlier on the road of emission reduction and have accumulated rich experience with relatively sound relevant laws and regulations. This paper studies and analyzes the emission reduction status of developed countries, and summarizes and summarizes the practical experience that can be used for reference from five aspects: scientific planning of emission reduction path, establishment and improvement of institutional system, gradual improvement of carbon price mechanism, breakthrough in energy conservation and emission reduction technology, and comprehensive implementation of circular economy. On this basis, combining with the current situation of economic and social development in China, Suggestions are put forward from four aspects: policy guidance, market mechanism, technological innovation and circular economy.